Breathing life into learning about air quality: developing and implementing environmental health outreach with high school students - Katie Hoskins; Nguyen Dang; Fahad Molla (Journal of the Medical Library Association)
Background: The San Joaquin Valley (SJV) is comprised of diverse populations that cumulatively are medically underserved and experience significant air pollution. The SVJ regularly has poor air quality and does not meet the state and federal attainment standards for particulate matter (PM) 2.5, ozone (eight hours), and PM 10. Air pollutants contribute to a high incidence of emergency room visits and hospitalizations for conditions like asthma. Because air pollutants correlate with built environments, these outcomes are concentrated geographically, which is a major driver of social determinants of health. Librarians from an osteopathic medical school in the SVJ developed an educational outreach session to inform high school students about the causes and health impacts of air pollution and how they can find resources to educate themselves and others in their communities.